T(y)ranslators – Agents of Authority and Censorship in Translation - Raluca GHENȚULESCU (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages, 2023)
Censorship and self-censorship in translation have been associated with oppressive regimes, although they are encountered in democratic systems as well. The agents and mechanisms behind these phenomena play a key part in spreading a certain ideology, which serves the interests of the ones in positions of power, be it political, economic or religious. The main purposes of this article are to analyse the criteria of censorship in translation, to illustrate the strategies used for censoring the potentially “dangerous” texts, to present case studies inspired by the realities of communist Romania and the contemporary American society, and to give examples of censorship agents, objectives and techniques.